EFEKTIVITAS PENGGUNAAN LAMPU DI DALAM WADAH KULTUR TABUNG AKRILIK PADA PERTUMBUHAN TETRASELMIS sp - Lessy, Abu Bakar; Pary, Bikri Rahman (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
This observation aims to determine the effectiveness of using TL lamps in acrylic culture containers and acrylic culture containers that do not use TL lamps on the growth of Tetraselmis sp. With a culture volume of 400 liters with the same organic technical fertilizer. The observation results showed the effectiveness of using the lamp in the culture container, there was a difference in the increase in cell density in the two culture containers where the C5 culture container using a TL lamp in the culture container had the highest/peak density of 152 x 104 cells/ml on the third culture day. However, on the fourth and fifth day it has begun to enter a decline phase and even reaches the death phase. Meanwhile, in the C6 culture container that did not use a TL lamp in the culture container, the peak density occurred on the second day with a density of 145 x 104 cells/ml, but in the C6 container, it experienced a decreasing phase until the death phase occurred on the third to fifth day. Keywords: Effectiveness, Growth, Tetraselmis sp